Литературный «билингвизм» как объект современных лингвопоэтических исследований - Кравцова, Юлия; Kravtsova, Yuliya (Східноєвропейський національний університет імені Лесі Українки, 2014)
Статтю присвячено актуальній проблемі лінгвопоетики – вивченню літературного «білінгвізму». Проана- лізовано наявні у цій сфері лінгвопоетичні дослідження, розглянуто питання про інтегральні та диференційні риси поезії і прози, особливості творчої реалізації письменника-«білінгва» в різних літературних формах та їх взаємозв’язок на рівні образно-експресивних засобів, специфіку мовної особистості поета-прозаїка.The article is devoted to the topical problem of linguistic poetics – study of literary «bilingualism». An analysis of existing linguopoetic researches in this field is presented, integral and differential characteristics of poetry and prose, peculiarities of creative realization of «bilingual» writer in these different literary forms and their relationship at the level of the figurative-expressive means, a specificity of language personality of the poet-and-prose writer are considered. Literary «bilingualism» (R. O. Jacobson) is a linguistic artistic phenomenon, consisting in the organic connection of poetry and prose in the creativity of one author. Study of the creative individuality of the poet-and-prose writer involves identifying various sides of his skill, determining common and specific features of artistic aesthetic realization of the author in both literary forms, establishing the degree of correlation and nature of interpenetration of the expression means in the poetic and prose texts, determined by the unity of language personality of the «bilingual» writer. Literary «bilingualism» is manifested in a number of specific characteristics – the existence of a «memory» of word, the increase of a degree of it's «freedom», «twins» contexts, the expansion of the range of semantic tools, the variety of the ways of artistic reflection of the reality, the originality of rhythmics. Linguistic personality of the «bilingual» writer is considered as a person with a high level of language competence, ability to literary creativity and artistic generalizations, special perception of the reality, that wields poetry and prose forms of verbal art. One of the most important parameters of the model of language personality of the «bilingual» writer is the level of language proficiency, including the features of individual selecting the linguistic means, variability of word usage, as focus on the «memory» of word etc. Another important indicator is the ability of a language personality to individual specific vision of the world, manifesting in a variety of ways of artistic reflection of the reality in poetry and prose, usage of various stylistic devices in various forms of verbal art. The essence of the artistic thinking of the «bilingual» writer is so that while there is a variability of the forms of creative expression, his language personality is remains uniform.
Literary «bilingualism» as an object of modern linguopoetic researches.
Keywords: літературний «білінгвізм»; письменник-«білінгв»; мовна особистість; образно-експресивні засоби; literary «bilingualism»; «bilingual» writer; language personality; figurative-expressive means